South-south cooperation - opportunities and challenges for international cooperation - Tatjana Chahoud (Deutsches Institut für Entwicklungspolitik (DIE), 2007)
Since China and India (“Asian drivers”) and other “rising powers,” especially Brazil and South Africa, began their steady climb, international cooperation has been faced not only with new opportunities, but also with a number of specific challenges. During the political debate new variants of colonial relations have also been identified from time to time. A sober look at South-South cooperation shows, however, that neither hasty condemnation nor euphoria is helpful: what is needed is an objective debate in which all the actors involved in development cooperation participate. To clarify the role of South-South cooperation, the following subjects are outlined: Current tendencies in South-South cooperation (trade, investment, finance) South-South cooperation: the role of the Asian drivers in African countries Prospects for South-South cooperation and recommendations for international cooperation. In the past decade South-South trade has expanded more quickly than North-South trade. South-South investment too has shown unprecedented dynamism. Investors from the South often have important regional know-how, use appropriate technologies and prove more willing to take business risks in a difficult political environment. A further indicator of the increased importance of South-South cooperation is the fact that countries in the South have become an additional source of official development assistance (ODA). The data on the actual scale of South-South development cooperation are still fragmentary, however.Current trade and investment flows between China and Africa are substantially driven by complementary structures in the two regions: African raw materials for Chinese industrial goods. In contrast, Indian trade and investment flows to Africa largely concern manufacturing industry and the service sector. Recently, however, India has similarly stepped up its foreign direct investment (FDI) in the oil sector. In China, India and most other countries in the South there is in fact no clear distinction between concessionary and commercial flows.In general, China's and India's development cooperation is well integrated into their foreign, economic and security policies. Conceptually, it is guided by the Bandung Principles, especially that of non-interference in the recipient country's internal affairs. Conditionality along the lines of the OECD/DAC's aid effectiveness concept is rejected by most countries of the South. While the positive sides of the current South-South dynamism are to be seen primarily in the increased inflows of resources, especially to the benefit of poor developing countries, many African states face major challenges because of increased dependence on raw materials and the greater pressure of competition from Asian countries in the case of light manufactures. The high-level dialogues between the G8 and the five leading anchor countries (Brazil, China, India, Mexico and South Africa) announced during the Heiligendamm process may help considerably to ensure that benefits are derived from closer South-South cooperation and that conceivable risks are discussed openly.
Keywords: 330